THE LAST RULER OF THE STATE OF ATABEKS OF AZERBAIJAN IN THE ARAB-PERSIAN SOURCES - Timohin, Dmitrij Mihajlovic (History, Archeology and Ethnography of the Caucasus, 2018)
Abstract. The article focuses on the last atabek of Azerbaijan Muzaffar ad-Din Uzbek, the history of whose reign, despite the existing studies, requires special attention. In this article, we try to analyze the description of the life and reign of this historical figure, trace the folding of his image in the Arab-Persian historical sources from different eras. Secondly, we would like to compare the image of the last atabek that was formed in the medieval written sources, with the descriptions of modern researchers. All this will allow for a better understanding of the image transformation of the last ruler of the state of atabeks of Azerbaijan. Another important task of this article is to analyze the evolution of the image of Muzaffar al-Din Uzbek in medieval historical sources and highlight the reasons why in some written monuments he is presented as a negative character or his personality, on the contrary, is subjected to “heroization”. Such an analysis of information from historical sources is impossible without the analysis of the historical context within which this or that text was formed. Finally, this kind of historical deconstruction will allow us to answer not only the question in connection with which this or that image of this historical figure was constructed but also to give an objective assessment of the life and work of the last ruler of the state of atabeks of Azerbaijan. We hope that this study will be useful not only for experts in the history of the South Caucasus of the Mongol invasion but also to a wide range of readers, interested in the medieval history of the region.